PREPOSISI DALAM KITAB KELUARAN - PONDAAG, ORLEN CHRISTIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This research entitled â€œPreposition in the Book of Exodusâ€ is written to identify and classify the forms as well as the meanings of the preposition found in the book of Exodus. The writer uses a theory from Aarts and Aarts (1982) to classify the forms of preposition and from Harman (1986) to analyze the meaning of prepositions. The method used in this research is descriptive method, and the data were taken from the book of Exodus based on The Holy Bible New International Version. The forms of the preposition found in the Book of Exodus are: simple preposition (one-word preposition) consisting of: at, before, from, in, between, by, during, of, on, since, until, and with, and complex prepositions (multi-word preposition) consisting of: according to, as to, because of, in addition to, in front of, and out of. Meanwhile, the meanings of prepositions found in this book are: cause or reason, condition, direction, instrument, manner, participation, place, purpose, source, and time. __________________________________________________________________ÂÂÂ_______ Key words: Preposition, Forms and Meanings, The Book of Exodus in the Bible